Application of the cognitive, communicative and sociocultural approach in the comprehension of literary texts in high school students - Tinta, Mario (2019)
The objective of the research was to determine the effectiveness of the cognitive, communicative and sociocultural approach in the comprehension of literary texts in secondary school students of the National Independence Secondary Education Institution, Puno, 2018. According to the predominant paradigm, the research was quantitative. Regarding the application strategy, it was experimental. The design used in the research was quasi - experimental, with two groups. The treatment was applied to the experimental group. The population consisted of 156 students. The sample consisted of 64 students. The technique that was used was the evaluation or measurement. The instrument that was used was the written test. The following conclusion was reached: The cognitive, communicative and sociocultural approach is effective in the comprehension of literary texts in the students. This conclusion is reached because the calculated Z is superior to the Z table: , so the alternative hypothesis is confirmed. Likewise, in the exit test the students are predominantly located on the "Achieved Achievement" scale with 16 students (50%), while in the entrance test the "On Start" scale predominated with 17 students (53%). The average of the entrance test was 7.19 and that of the exit test was 17.03.